2016
DOI: 10.1177/0023677216661586
|View full text |Cite
|
Sign up to set email alerts
|

Murine norovirus detection in the exhaust air of IVCs is more sensitive than serological analysis of soiled bedding sentinels

Abstract: One limitation to housing rodents in individually ventilated cages (IVCs) is the ineffectiveness of traditional health monitoring programs that test soiled bedding sentinels every quarter. Aerogen transmission does not occur with this method. Moreover, the transmission of numerous pathogens in bedding is uncertain, and sentinel susceptibility to various pathogens varies. A novel method using particle collection from samples of exhaust air was developed in this study which was also systematically compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 13 publications
1
33
1
Order By: Relevance
“…8 To solve these problems, methods that assess sentinel exposure by surveying the exhaust air of IVC have been reported. 4,6,18,19,26 However, if a pathogenic microbe is detected in animal rooms, sentinels as well as experimental animals must be examined to identify sources of infection or sensitive hosts. In most cases, experimental animals need to Vol 58, No 6 Journal of the American Association for Laboratory Animal Science November 2019 be evaluated without euthanizing them because the number of maintenance strains is increasing and because few animals of each strain are cohoused.…”
Section: Discussionmentioning
confidence: 99%
“…8 To solve these problems, methods that assess sentinel exposure by surveying the exhaust air of IVC have been reported. 4,6,18,19,26 However, if a pathogenic microbe is detected in animal rooms, sentinels as well as experimental animals must be examined to identify sources of infection or sensitive hosts. In most cases, experimental animals need to Vol 58, No 6 Journal of the American Association for Laboratory Animal Science November 2019 be evaluated without euthanizing them because the number of maintenance strains is increasing and because few animals of each strain are cohoused.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaust debris PCR monitoring of IVC racks has recently been evaluated for its efficacy in detecting several pathogens. 2,5,8,17,19,22,25,[27][28][29]39 Most commonly, the studies found that detection through PCR analysis of exhaust debris was a reliable option or a good adjunct to a health monitoring program. Notably, PCR evaluation of exhaust debris was found to be reliable and in some cases superior in detecting mouse hepatitis virus, Sendai virus, Helicobacter spp., Rodentibacter pneumotropicus and heylii (previously Pasteurella pneumotropica), 3 pinworms, fur mites, and enteric protozoa.…”
mentioning
confidence: 99%
“…To be able to study NoV viability, the cultivable murine norovirus (MNV) is frequently used as a model 7,8 . Moreover, MNV infections are a common problem in mice in laboratory animal facilities 9 .…”
mentioning
confidence: 99%